Disruption of Glutamate-Glutamine-GABA Cycle Significantly Impacts on Suicidal Behaviour: Survey of the Literature and Own Findings on Glutamine Synthetase. - Bernstein, Hans-Gert; Tausch, Anne; Wagner, Rebecca; Steiner, Johann; Seeleke, Patrick; Walter, Martin; Dobrowolny, Henrik; Bogerts, Bernhard (CNS & Neurological Disorders - Drug Targets, 2013)
The aetiology of suicide is complex and still not completely understood. The present communication, which consists of two parts, aims to shed some light on the role of amino acidergic neurotransmission in suicide. In the first part we provide an overview of the literature showing that with the exception of certain gamma-aminobutyric acid transporters, virtually all components of the glutamate-glutamine- gamma-aminobutyric acid cycle are, in some way or other, abnormal in suicide victims, which indicates a prominent involvement of the glutamatergic and gammaaminobutyric acidergic neurotransmitter systems in suicidal behaviour. In the second part we present own immunohistochemical findings showing that densities of glutamine synthetase expressing glial cells in the mediodorsal thalamus as well as in the dorsolateral prefrontal and orbitofrontal cortex of schizophrenic suicide completers are significantly elevated compared with controls and non-suicide individuals with schizophrenia, thus calling into question the belief that cerebral glutamine synthetase deficit is indicative of suicidal behaviour.
Keywords: Gamma-aminobutyric acid